2007
DOI: 10.1074/jbc.m608980200
|View full text |Cite
|
Sign up to set email alerts
|

Src Utilizes Cas to Block Gap Junctional Communication Mediated by Connexin43

Abstract: Src is a membrane-bound tyrosine kinase that triggers the transformation of normal cells into cancer cells (1). Src has been implicated a variety of human cancers (2, 3). As expected, metastatic cell growth is significantly reduced by agents that inhibit Src kinase activity (4, 5).Increased anchorage-independent growth and migration distinguish most cancer cells from their nontransformed precursors (6, 7). The Src kinase phosphorylates Cas (Crkassociated substrate) to promote these fundamental hallmarks of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
1
32
0
1
Order By: Relevance
“…We demonstrated that activation of Src kinase leads to a decrease in communication between cells, consistent with its oncogenic role in metastasis. The dynamic behavior of proteins downstream of Src, such as connexin 43 or Cas, that are involved in intercellular communication (34), will be the subject of future study.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that activation of Src kinase leads to a decrease in communication between cells, consistent with its oncogenic role in metastasis. The dynamic behavior of proteins downstream of Src, such as connexin 43 or Cas, that are involved in intercellular communication (34), will be the subject of future study.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Activation of the protein tyrosine kinase pathway was shown to suppress I Na and to reduce conductance through the gap junction . 42,43 Further investigation is warranted to delineate the exact signaling pathway(s) responsible for VIP effects on individual ion channels.…”
Section: Molecular Basis Of Vip Effectsmentioning
confidence: 99%
“…SRC was shown to bind to the Src-binding site and to phosphorylate several YXXP motifs of BCAR1 [30][31][32][33]. These experiments have shown that BCAR1 phosphorylation may be important for some processes (cell migration), but not essential for anchorage-independent growth of SRC transformed fibroblasts [7,23,24,[34][35][36]. Another important finding was the functional association between the C-terminal ends of BCAR1 and BCAR3 (AND-34) [37][38][39][40][41], the latter also identified in our functional screen for tamoxifen resistance [42].…”
Section: Introductionmentioning
confidence: 99%